2019
DOI: 10.1101/778761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction between polygenic liability for schizophrenia and childhood adversity influences daily-life emotional dysregulation and psychosis proneness

Abstract: AbstractBackgroundThe earliest stages of the pluripotent psychopathology on the pathway to psychotic disorders is represented by emotional dysregulation and subtle psychosis expression, which can be measured using the Ecological Momentary Assessment (EMA). However, it is not clear to what degree common genetic and environmental risk factors for psychosis contribute to variation in these early expressions of psychopathology. Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…A recent study demonstrated that intra‐uterine environment moderates the association between PRS‐SCZ and schizophrenia, and further revealed in the pathway analysis that genes involved in cellular stress response were the main drivers of the gene‐environment interaction. In our recent study of a general population twin cohort, we found evidence for positive interaction effects between PRS‐SCZ and exposure to childhood adversities to pleiotropically influence momentary emotional regulation and psychosis proneness. Further, a multimodal study combining genetics and imaging techniques reported that the association between PRS‐SCZ and cortical maturation in young male adults is moderated by early‐life exposure to cannabis.…”
Section: Discussionmentioning
confidence: 57%
“…A recent study demonstrated that intra‐uterine environment moderates the association between PRS‐SCZ and schizophrenia, and further revealed in the pathway analysis that genes involved in cellular stress response were the main drivers of the gene‐environment interaction. In our recent study of a general population twin cohort, we found evidence for positive interaction effects between PRS‐SCZ and exposure to childhood adversities to pleiotropically influence momentary emotional regulation and psychosis proneness. Further, a multimodal study combining genetics and imaging techniques reported that the association between PRS‐SCZ and cortical maturation in young male adults is moderated by early‐life exposure to cannabis.…”
Section: Discussionmentioning
confidence: 57%
“…Studies in healthy participants have shown inconsistent results (Hatzimanolis et al ., 2015; Jones et al ., 2016; Mistry et al ., 2017; Nivard et al ., 2017; Riglin et al ., 2017; Hatzimanolis et al ., 2018), one study notably reporting negative associations between polygenic risk and schizotypy, similar to the current results (Hatzimanolis et al ., 2018). Another recent general population study found a protective effect of PRS in that PRS predicted greater levels of positive affect in daily life (Pries et al ., 2019). It is likely that crucial variation may be occasioned by type of platform for genetic analysis and type of calculation of polygenic risk score.…”
Section: Discussionmentioning
confidence: 99%
“…recent concepts of psychopathology acknowledge that the development of mental disorders is best understood when also looking at micro, complex, moment-to-moment dynamic changes (van Os, Verhagen et al, 2017). Therefore, Pries, Klingenberg et al (2019) investigated whether molecular genetic risk for schizophrenia interacted with CA and daily life stressors to influence moment-to-moment variations of mental states (i.e., negative affect, positive affect and subtle psychosis expression) and stress sensitivity. Molecular genetic vulnerability was expressed through polygenic risk score (PRS) for schizophrenia, which was calculated by summing weighted trait-alleles (EUGEI investigators, 2014;Purcell et al, 2009;Ripke et al, 2014).…”
Section: Genetic and Nongenetic Risk Factorsmentioning
confidence: 99%
“…They highlight the role of gene-environmental interaction focusing both on macro and micro levels of psychopathological changes, that is, changes occurring over month and years (Lecei et al, 2019;Pinckaers et al, 2019;Vaessen et al, 2017) and from moment to moment (Hasmi et al, 2017;Pries, Klingenberg et al, 2019;Vaessen et al, 2017), respectively. It is increasingly acknowledged that the development of pleiotropic psychopathology depends on a complex network of environmental exposures, that is, the exposome (Guloksuz et al, 2018;Pries, Lage Castellanos et al, 2019), and polygenic vulnerability (Guloksuz et al, 2019), which affect individuals throughout their life. Similarly, resilience is thought to dynamically change and can only be understood by prospectively evaluating different biological and psychological processes (Kalisch et al, 2017;Rutten et al, 2013;Snijders et al, 2018).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation